Strategi Meningkatkan Minat Beli Konsumen Produk Aerostreet melalui Periklanan di Media Sosial TikTok - Erwin Permana; Davina Putri Aulia; Ridwan Roy Tutupoho (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
The development of social media has encouraged the growth of local fashion brand businesses, including Aerostreet. This shoe brand has succeeded in utilizing TikTok as its main marketing strategy, outperforming other platforms. This research analyzes the strategy of increasing Aerostreet consumer buying interest through advertising on TikTok using digital observation methods, content analysis and secondary data. The research results show that strategies such as In-Feed Ads, Branded Hashtag Challenge, collaboration with influencers, and the use of For You Page (FYP) are effective in increasing brand awareness, engagement, and consumer trust. Creative content and storytelling also play a role in increasing sales conversions. These findings prove that digital marketing on TikTok can help local brands expand their market and increase their competitiveness. For further effectiveness, Aerostreet is advised to continue to innovate in content creation and expand collaboration with appropriate influencers and Key Opinion Leaders (KOL).